ANALYSIS OF DETERMINANTS OF MSMEs TAX COMPLIANCE IN INDONESIA (CASE-STUDY IN WORKING AREAS OF PONDOK AREN TAX OFFICE) - Suparna Wijaya, Aghnia Silviani Effendi (International Journal of Advanced Science and Technology, 2020)
The tax revenue target in Indonesia from 2012 to 2018 has never been received. Likewise, the realization of the level of taxpayers starting in 2013 until 2018, has still not reached 100%. One of the contributors to tax revenue is MSMEs, which provide a large agreement for Indonesia's GDP. Pondok Aren Tax Office is one of the tax office that won the development and assistance of MSMEs. Hence, This study aims to analyze the tax compliance determinants in the form of attitudinal influence on the electronic tax system, electronic tax system adoption, tax fairness, isomorphic strength, and strategic response to MSME tax compliance in the Pondok Aren Tax Office work area. The data used are primary data obtained from the answers to the respondents’ questionnaires. Testing statistics on data using the SPSS application. The sample used is the Personal MSME Taxpayer. The results showed that the adoption of the electronic tax system, tax justice, isomorphic strength, and strategic response affected the tax compliance of MSMEs in the Pondok Aren Tax Office work area, while the attitude about the electronic tax system had no effect.